Jawabanmu

2014-08-11T21:37:28+07:00
F(x) = (x - 2)(x + 2) . h(x) + s(x)
f(x) = (x - 2)(x + 2) . h(x) + px + q

bila dibagi oleh x-2 mempunyai sisa 5 maka x = 2

f(x) = (x - 2)(x + 2) . h(x) + px + q
f(2) = (2 - 2)(2 + 2) . h(x) + 2p + q
5 = 0 + 2p + q
5 = 2p + q

bila dibagi oleh x+2 mempunyai sisa 10 maka x = -2

f(x) = (x - 2)(x + 2) . h(x) + px + q
f(-2) = (-2 - 2)(-2 + 2) . h(x) - 2p + q
10 = 0 - 2p + q
10 = - 2p + q


-2p + q = 10
2p + q = 5     +
2q = 15
q = 15/2

2p + q = 5
2p + 15/2 = 5
2p = 5 - 15/2
2p = -5/2
p = -5/4

sisa pembagian = S(x)
                               = px + q
                               = -5/4q + 15/2